2010
DOI: 10.1099/mic.0.034744-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and glucose 6-phosphate as carbon sources in extra- and intracellular growth of enteroinvasive Escherichia coli and Salmonella enterica

Abstract: To study the role of carbohydrates, in particular glucose, glucose 6-phosphate and mannose, as carbon substrates for extra-and intracellular replication of facultative intracellular enteric bacteria, mutants of two enteroinvasive Escherichia coli (EIEC) strains and a Salmonella enterica serovar Typhimurium isolate were constructed that were defective in the uptake of glucose and mannose (DptsG, manXYZ ), glucose 6-phosphate (DuhpT ) or all three carbohydrates (DptsG, manXYZ, uhpT ). The ability of these mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…Carbohydrate metabolism has also been implicated in pathogenesis of enteroinvasive E. coli (EIEC), which is closely related to Shigella. In a cell culture model, an EIEC mutant defective in both glucose and mannose transport was significantly impaired in adherence and invasion (15). The intracellular pathogen Listeria monocytogenes appears to maximize its ability to grow intracellularly by using multiple carbon sources, such as glucose-6-phosphate and glycerol (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate metabolism has also been implicated in pathogenesis of enteroinvasive E. coli (EIEC), which is closely related to Shigella. In a cell culture model, an EIEC mutant defective in both glucose and mannose transport was significantly impaired in adherence and invasion (15). The intracellular pathogen Listeria monocytogenes appears to maximize its ability to grow intracellularly by using multiple carbon sources, such as glucose-6-phosphate and glycerol (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate phosphotransferase systems were encoded by the genes ptsG/crr, manXYZ, fruBA, malX/crr, scrA/crr, and bglF, and glucose 6-phosphate was taken up by both pathogens via the UhpT transporter, which is under the control of a complex two-component system (uhpABC). S. Typhimurium mutants defective for the uptake of glucose and mannose (⌬ptsG manXYZ) and glucose 6-phosphate (⌬uhpT) have less capability for intracellular replication in undifferentiated Caco-2 cells, and the ⌬ptsG manXYZ uhpT triple mutant is still able to replicate within the vacuoles (398).…”
Section: Cell Interaction Cell Entry and Intracellular Lifestylementioning
confidence: 99%
“…EIEC strains growing in the cytosol of undifferentiated confluent Caco-2 cells utilize glucose, but not glucose 6-phosphate, or other phosphorylated carbohydrates, gluconate, or fatty acids as their main carbon substrates (397,398) (Table 2). Moreno et al (440) have compared the intracellular lifestyle of EIEC within fully differentiated Caco-2 cells at the cellular and molecular levels to that of S. flexneri.…”
Section: Cell Interaction Cell Entry and Intracellular Lifestylementioning
confidence: 99%
“…However, at this stage of the work, we cannot totally exclude the possibility that exSPs would directly enter the cell via specific transporters similar to the uhp system (Götz and Göbel 2010) and controlled by PhoP. This hypothesis seems unlikely since a genomic scale analysis of possible carbohydrate transporters (Bertram et al 2004) did not identified, in S. coelicolor, an uhp-like uptake system.…”
Section: Discussionmentioning
confidence: 89%
“…The utilization of sugar phosphates is PhoPdependent Theoretically, exSPs could be up-taken as such by a specific transporter similar to the uhp (uptake of hexose phosphate) system of enteroenvasive Escherichia coli and Salmonella enterica (Götz and Göbel 2010).…”
Section: Effect Of Extracellular Sugar-phosphates On Streptomyces Devmentioning
confidence: 99%